Cadmium sulfide quantum dots induce oxidative stress and behavioral impairments in the marine clam Scrobicularia plana. (12th May 2015) - Buffet, Pierre‐Emmanuel; Zalouk‐Vergnoux, Aurore; Poirier, Laurence; Lopes, Christelle; Risso‐de‐Faverney, Christine; Guibbolini, Marielle; Gilliland, Douglas; Perrein‐Ettajani, Hanane; Valsami‐Jones, Eugenia; Mouneyrac, Catherine
Abstract Cadmium sulfide (CdS) quantum dots have a number of current applications in electronics and solar cells and significant future potential in medicine. The aim of the present study was to examine the toxic effects of CdS quantum dots on the marine clam Scrobicularia plana exposed for 14 d to these nanomaterials (10 µg Cd L–1) in natural seawater and to compare them with soluble Cd. Measurement of labile Cd released from CdS quantum dots showed that 52% of CdS quantum dots remained in the nanoparticulate form. Clams accumulated the same levels of Cd regardless of the form in which it was delivered (soluble Cd vs CdS quantum dots). However, significant changes in biochemical responses were observed in clams exposed to CdS quantum dots compared with soluble Cd. Increased activities of catalase and glutathione‐S‐transferase were significantly higher in clams exposed in seawater to Cd as the nanoparticulate versus the soluble form, suggesting a specific nano effect. The behavior of S. plana in sediment showed impairments of foot movements only in the case of exposure to CdS quantum dots. The results show that oxidative stress and behavior biomarkers are sensitive predictors of CdS quantum dots toxicity in S. plana. Such responses, appearing well before changes might occur at the population level, demonstrate the usefulness of this model species and type of biomarker in the assessment of nanoparticle contamination in estuarine ecosystems. Environ Toxicol Chem 2015;34:1659–1664. © 2015 SETAC